2011
DOI: 10.5897/ajmr11.206
|View full text |Cite
|
Sign up to set email alerts
|

Study of genetic diversity in Mycobacterium tuberculosis by using mycobacterial interspersed repetitive unit: Variable number tandem repeat typing in Khuzestan Province, Iran

Abstract: To investigate the genetic diversity of Mycobacterium tuberculosis (MTB) strains MIRU-VNTR as a powerful tool was used. In this study 80 isolates from patients were analyzed using primers based on IS6110 gene fragment specific for MTB complex. Then RD typing based on regions of difference was used to differentiate MTBC members. The MTB isolates were genotyped by 12 loci based MIRU-VNTR. The discriminatory index for each loci was calculated using the Hunter Gaston Discriminatory Index (HGDI).Of these, 60 cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…This information showed the most similarity of Sistan-Baluchestan province with isolates of Hormozgan that can explain the possibility of transmission of MTB from other provinces especially this province and vice versa [27]. There was no similarity between the patterns found in this study and those formerly reported from East Azerbaijan province and Khuzestan province [35, 36]. Moreover the MIRU-VNTR profiles did not match any strain in the MIRU-VNTRplus database and were debated unrelated to reference strains.…”
Section: Discussionmentioning
confidence: 51%
“…This information showed the most similarity of Sistan-Baluchestan province with isolates of Hormozgan that can explain the possibility of transmission of MTB from other provinces especially this province and vice versa [27]. There was no similarity between the patterns found in this study and those formerly reported from East Azerbaijan province and Khuzestan province [35, 36]. Moreover the MIRU-VNTR profiles did not match any strain in the MIRU-VNTRplus database and were debated unrelated to reference strains.…”
Section: Discussionmentioning
confidence: 51%
“…Among MIRU loci in hospitals of Paris, France, locus 40 (h = 0.74) showed the highest variation (9). In three provinces in Iran, locus 16 (h = 0.64) exhibited the greatest variation (21), whereas in the province of Khuzestan in Iran, locus 31 (h = 0.73) displayed the highest variation (22). In a genotyping study of M. tuberculosis in China, locus C (h = 0.54) had the highest variation among ETR loci (23).…”
Section: Discussionmentioning
confidence: 98%
“…In a study of TB cases in Singapore, Sun et al (25) reported a discriminatory power of 0.994 for 68 cases. Studies of TB cases performed in Khoozestan province in Iran, Taiwan, and Samara in Russia reported a discriminatory power of 0.991 for 61 cases, 0.972 for 502 cases, and 0.625 for 129 cases, respectively (22, 24, 26). As the study in Singapore was based on a small number of isolates, its discriminatory power was slightly lower than in the present study.…”
Section: Discussionmentioning
confidence: 99%